Forestry and reindeer husbandry in northern Sweden – the development of a land use conflict - Widmark, Camilla (Rangifer, 2009)
Both the forestry sector and reindeer herders in northern Sweden use the forest resources in northern Sweden, albeit for different purposes, and have adverse effects on each other. To reduce conflicts between them negotiations take place in so-called “consultations”, but the institutional arrangement does not seem to be working well; the conflicts have not been resolved, and the reindeer herders are generally more dissatisfied with the outcome than the forest companies. This paper provides an overview of the parallel development of forestry and reindeer herding in the region. In addition several issues that complicate the consultations and need to be resolved in order to secure the continued co-existence of the two activities are identified, based on an analysis of physical, societal and judicial aspects of the relationship between them.Abstract in Swedish / Sammandrag:Skogsbruk och rennäringen i norra Sverige – utveckling av en markanvändningskonflikt Skogsresursen i norra Sverige nyttjas för bland annat timmerproduktion och renbete och skogsbruket respektive rennäring påverkar varandra negativt. För att minska konflikterna har samråd instiftats men processen fungerar inte tillfredsställande eftersom det finns ett missnöje bland renskötarna. Denna studie ger en översikt av den parallella utvecklingen av de två näringarna och deras inbördes relationer och därmed identifieras flera nyckelområden som komplicerar relationen mellan de båda näringarna och därmed även samråden. Genom att analysera de fysiska, sociala och juridiska aspekterna av relationen mellan rennäring och skogsbruk pekar studien på ett antal problem som måste lösas för att kunna säkerställa en fortsatt parallell existens.